Strategies for Developing Early Childhood Multiple Intelligence in the Family Environment - I Komang Wisnu Budi Wijaya (Journal of Childhood Development, 2024)
This study aims to analyze strategies for developing multiple intelligences in early childhood within the family environment. As a literature review, this research utilizes various sources such as books, journals, proceedings, and scientific articles related to multiple intelligences, early childhood development, and the role of family education. Data were analyzed using content analysis techniques. The results show that the development of multiple intelligences in early childhood within the family environment can be optimized through the active role of parents in stimulating various intelligences, including logical, linguistic, kinesthetic, social, and emotional intelligence. An approach focused on children's interests and talents, accompanied by activities such as educational games, motor skill exercises, and open communication, can support holistic and balanced intelligence development. The implementation of these strategies is expected to help young children achieve optimal development across various intelligence aspects.